ASSESSMENT OF RISK FACTORS AND DETERMINING THE LEVEL OF PREVENTABLE FETAL DEATH IN WOMEN WITH TROUBLED PREGNANCY - M.YA. KAMILOVA; P.A. DZHONMAKHMADOVA; F.R. ISHAN-KHODZHAEVA (Avicenna Tajik State Medical University, 2020)
Objective: To examine the risk factors of stillbirth in the Republic of Tajikistan. Methods: Maps of individual observation of the course of pregnancy and the history of births of women with antenatal and intranatal fetal death in institutions of III and II levels have been studied. Retrospectively has been conducted the clinical audit of 187 cases of stillbirth. Results: The main causes of stillbirths were intrauterine growth retardation syndrome and fetal malformations. The most common risk factors for stillbirth were factors associated with inadequate medical care and factors related to family and women. At the same time, most of the cases of antenatal fetal death (83%) and intranatal fetal death (74%) were preventable or conditionally preventable. Conclusion: Our research confirms the need for perinatal audit, which aims to find the causes and risk factors of stillbirth with the subsequent implementation of solutions to prevent such cases of stillbirths in the future.